2018
DOI: 10.26442/terarkh2018909144-150
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency and cardiovascular pathology

Abstract: Vitamin D deficiency is widespread worldwide and present in about 30-50% of population. In most cases, this problem is associated with musculoskeletal system pathology: rickets in children, and osteomalacia or osteoporosis in adults. However, in recent years, convincing data was obtained on the links between vitamin D deficiency and cardiovascular pathology. Low Vitamin D levels in humans are associated with the unfavorable cardiovascular risk factors, such as arterial hypertension (AH), diabetes mellitus, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
4

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 43 publications
0
10
0
4
Order By: Relevance
“…Vitamin D is a group of organic chemical compounds belonging to the group secosteroids, among which calcitriol (1,25-dihydroxycholecalciferol) performs the highest biological (hormonal) activity [26,141]. Vitamin D is currently at the center of research interest for many scientists due to its widespread deficiency, reaching about 30-50% on a global scale, especially in older age groups [19,142]. Many scientists have been involved in the research on the discovery and description of vitamin D properties.…”
Section: Vitamin D-function and Antioxidant Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin D is a group of organic chemical compounds belonging to the group secosteroids, among which calcitriol (1,25-dihydroxycholecalciferol) performs the highest biological (hormonal) activity [26,141]. Vitamin D is currently at the center of research interest for many scientists due to its widespread deficiency, reaching about 30-50% on a global scale, especially in older age groups [19,142]. Many scientists have been involved in the research on the discovery and description of vitamin D properties.…”
Section: Vitamin D-function and Antioxidant Effectmentioning
confidence: 99%
“…Recently, attention has been paid to radioprotective properties of two hormones, whose synthesis depends on the specific light wavelengths, namely melatonin and vitamin D [ 17 , 18 ]. Both substances are endogenous compounds, but their deficiencies have been widely described in modern societies [ 19 , 20 ]. Melatonin as a strong direct and indirect antioxidant has been considered a radioprotector since the beginning of the 21st century [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Low bone mass has been reported to be related to cardiovascular diseases 5 . It has been found that osteoporosis and HF share common risk factors, such as advanced age, vitamin D deficiency, renal disease and other comorbidities 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…It is now widely accepted that adequate vitamin D levels should be maintained in all life stages, from fetal development to old age. Low vitamin D status has been associated with an increased risk of rickets, osteoporosis, diabetes mellitus, cardiovascular disease, depression, autoimmunity and even pregnancy complications 5–12. Low prenatal and early life vitamin D levels may also increase susceptibility to schizophrenia and multiple sclerosis (MS) in later life 13–15.…”
Section: Introductionmentioning
confidence: 99%